2019
DOI: 10.1039/c9sc04300d
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum targeting fluorescent probes to image mobile Zn2+

Abstract: Zn 2+ plays an important role in the normal function of the endoplasmic reticulum (ER) and its deficiency can cause ER stress, which is related to a wide range of diseases. In order to provide tools to better understand the role of mobile Zn 2+ in ER processes, the first custom designed ER-localised fluorescent Zn 2+ probes have been developed through the introduction of a cyclohexyl sulfonylurea as an ER-targeting unit with different Zn 2+ receptors. Experiments in vitro and in cellulo show that both probes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 73 publications
0
28
0
Order By: Relevance
“…The restriction of intramolecular rotations can also hinder the access to low energy conical intersections associated with ultrafast decay to the ground state. This theory was used to explain similar previous findings by us 6,22,31 and has been discussed elsewhere. 33,34…”
Section: Dft Calculationsmentioning
confidence: 65%
See 2 more Smart Citations
“…The restriction of intramolecular rotations can also hinder the access to low energy conical intersections associated with ultrafast decay to the ground state. This theory was used to explain similar previous findings by us 6,22,31 and has been discussed elsewhere. 33,34…”
Section: Dft Calculationsmentioning
confidence: 65%
“…S3 and Table S1, ESI), which is consistent with previous values we have observed in related probes with this zinc-binding motif and fluorophore. 6,22 A titration of probe 1 with different equivalents of Zn 2+ by 1 H NMR spectroscopy ( Fig. S4-S6, ESI) was performed to further demonstrate the Zn 2+ association.…”
Section: Photophysical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Glibenclamide functions as the ER targeting group in the commercial ER tracker red and ER tracker green, and using a sulfonyl urea analogue, we developed two probes 25 and 26 as ER targeting probes. 66 It was shown that both probes accumulated in the ER in a number of cell lines, and displayed a good switch on uorescence response to Zn 2+ . Probe 25 was used to demonstrate that a decrease of mobile Zn 2+ concentration in the ER occurs under conditions of ER stress induced by tunicamycin and thapsigargin.…”
Section: Endoplasmic Reticulum (Er) Targetingmentioning
confidence: 99%
“…[6][7][8][9][10][11] As a powerful technology which can provide spatiotemporal information on Zn 2+ , uorescence imaging has been applied in living cells, tissues and model animals. [12][13][14][15][16] Imaging and monitoring labile Zn 2+ uctuation is intriguing yet challenging since the deviation of endogenous labile Zn 2+ homeostasis might be very small and dynamic. Moreover, interference from photobleaching, sensor concentration variation, and light scattering may result in misleading information.…”
Section: Introductionmentioning
confidence: 99%